Technical Efficiency of Red Rice Farming in Gunung Kidul Regency, Yogyakarta - Rahayu Lestari (EDP Sciences, 2021)
Red rice is germplasm in Gunung Kidul Regency, whose territory is north, central, and south. This study aimed to analyze the factors that influence the production of red rice farming in Gunung Kidul Regency, analyze the level of technical efficiency, and the factors that influence the technical inefficiency of red rice farming in Gunung Kidul Regency. This research was conducted in Gunung Kidul Regency, which was determined purposively, in sampling 200 respondents. Data were analyzed using the Cobb-Douglas Stochastic Frontier model production function. The results showed that the variable area of land, seeds, manure, phonska fertilizer, urea fertilizer, liquid pesticides, and labor had a significant effect on the production of red rice. Technically, farmers have been efficient, with an average index of 0.837. Meanwhile, from the five internal factors of farmers, age, formal education, farming experience, dummy zones in the north, dummy zones in the south, no effect on inefficiency